Polycaprolactone spheres and theromosensitive pluronic F127 hydrogel for vocal fold augmentation: In vivo animal study for the treatment of unilateral vocal fold palsy. (31st January 2013) - Kwon, Seong Keun; Song, Jae‐Jun; Cho, Chang Gun; Park, Seok‐Won; Choi, Soo Jung; Oh, Se Heang; Lee, Jin Ho
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The purpose of this study was to explore a novel strategy to restore vocal gap by using polycaprolactone (PCL) spheres with thermosensitive Pluronic F127 in a paralyzed rabbit vocal fold. Study Design In vivo study using a rabbit model. Methods The PCL spheres were fabricated by an isolated particle‐melting method. The PCL spheres/Pluronic F127 gel mixture was prepared by a simple mixture of PCL and Pluronic F127 solution. We used 33 New Zealand white rabbits, which were divided into normal (n = 3), vocal fold palsy (VFP, n = 12), PCL/Pluronic F127 gel mixture (PCL, n = 12), and Radiesse (n = 6) groups. After unilateral recurrent laryngeal nerve section, PCL or Radiesse were injected into paralyzed vocal folds. Laryngoscopic exams were performed 1, 2, 4, and 12 weeks after implantation; then larynx specimens were sampled. High‐speed camera recording of vocal fold vibration and evaluation by videokymography were performed. Open quotient and asymmetric index were calculated. We evaluated the volume of the implants over time and investigated histologic changes. Results Endoscopic analysis showed that PCL/Pluronic F127 gel mixture maintained its volume without migration or inflammatory response. Vocal fold gap decreased and asymmetric vocal fold movement was improved compared with the VFP group. Histologically, connective tissue growth was observed between the spheres. The remaining volume of injected material was greater than the Radiesse group, without statistical significance. Conclusions Locally injected PCL/Pluronic F127 can enhance glottal contact, suggesting it as a potential new therapeutic approach that may lead to better treatment of vocal fold palsy. Level of Evidence N/A. Laryngoscope, 2013